1999
DOI: 10.1046/j.1432-1327.1999.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine modulates polyamine content in hepatocytes by inducing spermidine/spermine acetyltransferase

Abstract: Agmatine has been proposed as the physiological ligand for the imidazoline receptors. It is not known whether it is also involved in the homoeostasis of intracellular polyamine content. To show whether this is the case, we have studied the effect of agmatine on rat liver cells, under both periportal and perivenous conditions. It is shown that agmatine modulates intracellular polyamine content through its effect on the synthesis of the limiting enzyme of the interconversion pathway, spermidine/spermine acetyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…Initial studies on apoptosis in thymocytes observed polyamine depletion as an unsuspected finding and hypothesized that polyamine depletion contributed to the activation of apoptosis (25). Agmatine depletes intracellular polyamine levels to suppress growth (4,16,22,29,46,59,68). Supplementation with the polyamine putrescine attenuates this effect (22,33,59).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies on apoptosis in thymocytes observed polyamine depletion as an unsuspected finding and hypothesized that polyamine depletion contributed to the activation of apoptosis (25). Agmatine depletes intracellular polyamine levels to suppress growth (4,16,22,29,46,59,68). Supplementation with the polyamine putrescine attenuates this effect (22,33,59).…”
Section: Discussionmentioning
confidence: 99%
“…Agmatine suppresses growth through the reduction of intracellular polyamine levels, which are required for growth, and inhibition of ornithine decarboxylase (ODC), the first and rate-limiting enzyme of polyamine biosynthesis, in all models studied to date (4,16,22,29,46,59,68). Reduction of cellular polyamine levels occurs by the induction of the polyamine autoregulatory protein antizyme (4,29,59), increasing activity of polyamine catabolism (16,68), and/or decreasing ODC activity by another mechanism, possibly by reduction of ODC translation (4,71). Furthermore, agmatine is transported into mammalian cells via the polyamine transport system (57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agmatine administration to tumor cells in vitro results in a suppression of cell proliferation (Satriano et al, 1998;Choi and Cho, 1999;Vargiu et al, 1999;Babal et al, 2001;Dudkowska et al, 2003;Higashi et al, 2004;Kribben et al, 2004;Molderings et al, 2004;Mayeur et al, 2005). At the intracellular level, agmatine-induced decrease of cell proliferation was shown to be due to a decrease in the intracellular levels of the polyamines putrescine, spermidine, and spermine (Satriano et al, 1998;Choi and Cho, 1999;Vargiu et al, 1999;Babal et al, 2001;Dudkowska et al, 2003;Higashi et al, 2004;Mayeur et al, 2005), which are pivotal for cell growth (Igarashi and Kashiwagi, 2000). The intracellular concentration of polyamines is controlled at several stages, including their biosynthesis and their uptake.…”
mentioning
confidence: 99%
“…The role of parasite-produced agmatine may be to act as a regulator of polyamine metabolism by inducing SSAT activity. Agmatine has been shown to act as a modulator of polyamine content in mammalian cells by inducing SSAT (28), a feature which is enhanced by low oxygen tensions (28); in this regard, it is significant that C. parvum sporozoites infect the crypts of the intestinal epithelium, a microaerophilic environment. The possible role of host cell arginase in converting DFMA into DFMO (23), which could block host ODC synthesis and thereby lower host cell polyamine availability to the parasite, is unlikely because we have previously shown that DFMO has no effect upon growth of the parasite in vitro (10), and we demonstrate in this study that DFMO alone at 20 mg/kg is incapable of curing or preventing C. parvum infection in a mouse model.…”
Section: Discussionmentioning
confidence: 99%